Restructuración técnico administrativa en la empresa Pretelli LTDA., ubicada en la ciudad de Bogotá (2017)
Initiated by the development of a diagnosis, using the methodology of the five forces of Portter, the company was analyzed in an external environment. Two tools were used for the internal analysis. The DOFA matrix that allowed us to establish how the company finds itself in the face of weaknesses, opportunities, strengths, and threats complemented by the tool provided by the Chamber of Commerce Autodiagnostic Business showing the results obtained and the improvements through a Radar chart.